Investigations of Properties of Soil-Aggregate Mixtures - Skrzypczak, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of this paper is the evaluation of the use of waste material, which is the native soil. On the example of the base ground taken from the village of Lipie (Podkarpackie voivodeship), soil-aggregate mixtures were prepared with a different degree of addition of natural aggregate.
Keywords: soil-aggregate mixture; strength parameters; grain-size distribution; optimal moisture; mieszanka glebowo-kruszywowa; parametry wytrzymałościowe; rozkład wielkości ziarna; wilgotność optymalna